2019
DOI: 10.1002/jcla.23108
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of pre‐operative circulating inflammatory cytokines with restenosis and rapid angiographic stenotic progression risk in coronary artery disease patients underwent percutaneous coronary intervention with drug‐eluting stents

Abstract: Background This study aimed to explore the associations of common inflammatory cytokine levels with restenosis and rapid angiographic stenotic progression (RASP) risk in coronary artery disease (CAD) patients underwent percutaneous coronary intervention (PCI) with drug‐eluting stents (DES). Methods Two hundred and ten CAD patients underwent PCI with DES were consecutively recruited, then pre‐operative serum levels of TNF‐α, IL‐1β, IL‐4, IL‐6, IL‐8, IL‐10, IL‐17A, IL‐21, and IL‐23 were determined by ELISA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Hyperactivation of pro-inflammatory patterns, mainly characterized by cytokine storm, may increase risk of restenosis in patients who underwent PCI with stent implantation due to CHD. As recently reported by Sun et al, pre-operative increased levels of IL-6, TNF-α, and IL-23 may efficiently predict risk of restenosis after PCI associated with drug-eluting stent (DES) implantation [59]. Besides ACS, the cardiovascular system may be involved in patients affected by heart failure due to hemodynamic decompensation and, in a small percentage of cases, acute myocarditis may occur without prior evidence of CVD due to ACE2 presence on cardiac myocytes, potentially leading to chronic dilated cardiomyopathy [55,60,61].…”
Section: Effects Of Sars-cov-2 On Cardiovascular Systemmentioning
confidence: 89%
“…Hyperactivation of pro-inflammatory patterns, mainly characterized by cytokine storm, may increase risk of restenosis in patients who underwent PCI with stent implantation due to CHD. As recently reported by Sun et al, pre-operative increased levels of IL-6, TNF-α, and IL-23 may efficiently predict risk of restenosis after PCI associated with drug-eluting stent (DES) implantation [59]. Besides ACS, the cardiovascular system may be involved in patients affected by heart failure due to hemodynamic decompensation and, in a small percentage of cases, acute myocarditis may occur without prior evidence of CVD due to ACE2 presence on cardiac myocytes, potentially leading to chronic dilated cardiomyopathy [55,60,61].…”
Section: Effects Of Sars-cov-2 On Cardiovascular Systemmentioning
confidence: 89%
“…Previous studies reported that plasma IL-12 concentrations are significantly increased in many types of atherosclerosis and atherosclerotic cardiovascular disease, including stable angina pectoris (SAP), non-ST segment elevation myocardial infarction (NSTEMI), ST-elevation myocardial infarction (STEMI), acute myocardial infarction (AMI), and gradually increased SAP, unstable angina pectoris (UAP), and AMI (Zhou et al, 2001;Correia et al, 2010;Lin et al, 2012;Yong et al, 2013;Chistiakov et al, 2015;Opstad et al, 2016;Zykov et al, 2016). Clinical data showed that patients with coronary artery disease exhibit higher circulating IL-23 levels (Lin et al, 2012;Abbas et al, 2015;Sun et al, 2019a). In coronary artery disease patients who underwent percutaneous coronary intervention (PCI) with drug-eluting stents (DES), subjects with in-stent restenosis show higher circulating IL-23 levels in peripheral blood mononuclear cells (PBMCs) (Khojasteh-Fard et al, 2012).…”
Section: Clinical Datamentioning
confidence: 99%
“…Despite its wide use, there are currently no soluble markers to evaluate PMC-induced hemodynamic improvement, nor clinical outcomes. Using cytokine levels to assess outcome of percutaneous coronary intervention has shown promising results ( 17 ). Our study is the first to evaluate the impact of PMC on plasma levels of a broader range of cytokines, chemokines and growth factors, together with the frequency of activated circulating T cell subpopulations.…”
Section: Resultsmentioning
confidence: 99%